Assessment of proliferation and apoptosis markers in patients with autoimmune thyroiditis - Sheremet, M. I.; Shidlovskyy, V. O.; Sydorchuk, L. P. (Journal of Education, Health and Sport, 2016)
Sheremet М. І., Shidlovskyy V. O., Sydorchuk L. P. Assessment of proliferation and apoptosis markers in patients with autoimmune thyroiditis. Journal of Education, Health and Sport. 2016;6(1):179-188. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45327 http://ojs.ukw.edu.pl/index.php/johs/article/view/45327 https://pbn.nauka.gov.pl/works/709555 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.12.2015. Revised 12.01.2016. Accepted: 25.01.2016. UDC 616.441-002: 616-002.18 ASSESSMENT OF PROLIFERATION AND APOPTOSIS MARKERS IN PATIENTS WITH AUTOIMMUNE THYROIDITIS М. І. Sheremet, V. O. Shidlovskyy*, L. P. Sydorchuk Bukovinian State Medical University, Chernivtsi, Ukraine *I.Y. Horbachevsky State Medical University, Ternopol, Ukraine Abstract The paper presents results of a comparative analysis of apoptosis and proliferative activity in the tissue of the thyroid gland (TG) in patients with autoimmune thyroiditis (AIT) and thyroid adenoma (TA) compared with morphologically unaltered thyroid tissue. In immunohistochemical study of the tissue we detected high proliferative activity of lymphoid tissue in patients with AIT, moderate proliferative activity of tissue in TA and low activity beyond it. In AIT one can notice intensive expression of Fas, Bcl-2 and Ki-67 compared to both morphologically unchanged tissue and the thyroid adenoma, which indicates immunological destruction of the thyroid epithelium. While studying combined indicators of apoptosis and proliferation in these patients we found out that in patients with AIT the number of all groups of connected cells is by 3-25 times higher as compared both to the group of patients with TA and to those with morphologically unchanged thyroid tissue. We also discuss possible mechanisms of the disorders found. Key words: thyroid gland, autoimmune thyroiditis, apoptosis, markers of proliferation.